Unpacking EFL Teacher Self-Efficacy in Livestream Teaching in the Chinese Context - Liu, Honggang; Chu, Wenxiu; Wang, Ye (Frontiers in Psychology, 2021)
Teacher self-efficacy has long been researched in the context of face-to-face teaching, but it has received less attention in regard to online teaching. To address this gap, the current study utilized a questionnaire adapted from Lin and Zheng (2015) as the major instrument and supplementary interviews to examine teacher self-efficacy in livestream teaching in the Chinese context. Exploratory factor analysis (EFA) results from 486 senior high school English as a foreign language (EFL) teachers in China yielded a two-factor structure of teacher self-efficacy comprising instructional self-efficacy and technological self-efficacy. Across the sample, EFL teachers had moderately high self-efficacy in general, and they showed higher levels of technological self-efficacy than instructional self-efficacy. The interview data also indicated a fluctuation in technological self-efficacy at the onset of livestream teaching compared to one month into livestream teaching. Ultimately, the results offer some useful suggestions for enhancing teacher self-efficacy.